2013
DOI: 10.1681/asn.2012080769
|View full text |Cite
|
Sign up to set email alerts
|

An In Vivo Functional Analysis System for Renal Gene Discovery in Drosophila Pericardial Nephrocytes

Abstract: The difficulty in accessing mammalian nephrons in vivo hinders the study of podocyte biology. The Drosophila nephrocyte shares remarkable similarities to the glomerular podocyte, but the lack of a functional readout for nephrocytes makes it challenging to study this model of the podocyte, which could potentially harness the power of Drosophila genetics. Here, we present a functional analysis of nephrocytes and establish an in vivo system to screen for renal genes. We found that nephrocytes efficiently take up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
135
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(136 citation statements)
references
References 33 publications
1
135
0
Order By: Relevance
“…The mitochondrial fractionation of podocytes was done using Mitochondrial Isolation Kit for Cultured Cells and UAS-RNAi transgenes (14,41). Nephrocyte function was measured by the amount of secreted red fluorescent proteins accumulated in nephrocytes at the second instar larvae stage (14,41).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mitochondrial fractionation of podocytes was done using Mitochondrial Isolation Kit for Cultured Cells and UAS-RNAi transgenes (14,41). Nephrocyte function was measured by the amount of secreted red fluorescent proteins accumulated in nephrocytes at the second instar larvae stage (14,41).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we performed knockdown of Drosophila coq8 (dcoq8) in Drosophila pericardial nephrocytes, which share remarkable similarities to the glomerular podocytes (14). The protein uptake assay showed that knockdown of dcoq8 in nephrocytes reduced the uptake ability of a secreted fusion protein of rat atrial natriuretic factor (ANF) and GFP, suggesting that dcoq8 is required for nephrocyte function in Drosophila (Supplemental Figure 2, A and B).…”
Section: Tablementioning
confidence: 99%
“…The proteinuric effect of the arhgdia MO was confirmed using an established zebrafish proteinuria ELISA assay (38) against a fusion protein of vitamin D-binding protein and GFP in /-fabp::VDBP-GFP transgenic zebrafish ( Figure 5E). Similarly, the protein uptake assay using Drosophila pericardial nephrocytes, which share remarkable similarities to the glomerular podocytes (39), showed that knockdown of Drosophila RhoGDI (CG7823) in nephrocytes reduced the uptake ability of the secreted fusion protein of rat atrial natriuretic factor (ANF) and GFP, suggesting that CG7823 is required for nephrocyte function in Drosophila (Supplemental Figure 9).…”
Section: Figurementioning
confidence: 97%
“…In Drosophila, mutations in duf and sns also result in loss of filtration diaphragms and in radical changes in nephrocyte architecture and function (Prieto-Sánchez, 2009;Weavers et al, 2009;Zhuang et al, 2009). Taking into account all the similarities previously described, we proposed that the nephrocyte filtration diaphragm could be a suitable model with which to study the formation, maintenance and repair of the vertebrate SD (Weavers et al, 2009) (a view supported by Dow and Romero, 2010;Simons and Huber, 2009;Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 94%